The Impact of Inflation on Financial Sector Performance: A Case Study of Sub-Saharan Africa - Tolulope, Apanisile Olumuyiwa; Oyeyinka, Oyelami Lukman (Indian Journal of Finance, 2014)
The study investigates the impact of inflation on financial sector performance in the sub-Saharan African region. To this end, dynamic panel data was employed, and the cross section covers 45 countries in the region between the period from 1980 - 2011. Three measures of financial sector performance (domestic credit to private sector, liquidity ratio, and market capitalization) were used for the study. Inflation was disaggregated to anticipated and unanticipated inflation, and the results show that both anticipated and unanticipated inflation have a negative effect on the financial sector performance, especially on the activities of the banking sector. The study, therefore, concludes that high inflation rate is inimical to financial sector performance, irrespective of the economy involved, and the government should employ necessary measures to control inflation as a way of improving the performance of the financial sector.